2015
DOI: 10.1017/s0007114515002135
|View full text |Cite
|
Sign up to set email alerts
|

Egg intake and cancers of the breast, ovary and prostate: a dose–response meta-analysis of prospective observational studies

Abstract: Evidence suggests that egg intake may be implicated in the aetiology of sex hormone-related cancers. However, dose-response relationships between egg intake and such cancers are unclear. Thus, we conducted a dose -response meta-analysis to summarise the dose -response relationships between egg consumption and the risk of breast, prostate and gynaecological cancers. A literature search was performed using PubMed and Embase up to April 2015 to identify relevant prospective observational studies. Summary relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 54 publications
(92 reference statements)
3
32
0
Order By: Relevance
“…Additionally, this is an updated meta-analysis to investigate the association between total red meat, fresh red meat, processed meat, fish, egg, soy food, and total milk intake and incidence of breast cancer. Although some previous meta-analyses [15,74,75,76,77] have investigated the association between total red meat, fresh red meat, processed meat, fish, egg, soy food, and total milk intake and incidence of breast cancer, many of them were based on highest versus lowest intake. Since then, a number of large-scale prospective studies were performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, this is an updated meta-analysis to investigate the association between total red meat, fresh red meat, processed meat, fish, egg, soy food, and total milk intake and incidence of breast cancer. Although some previous meta-analyses [15,74,75,76,77] have investigated the association between total red meat, fresh red meat, processed meat, fish, egg, soy food, and total milk intake and incidence of breast cancer, many of them were based on highest versus lowest intake. Since then, a number of large-scale prospective studies were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Third, different studies used different units (such as servings and times). Although we converted these units into grams per day according to standard conversions from the Food Standards Agency [13] and other documents [14,15,16], this could still influence the association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies help generating hypotheses and exploring associations between diet and health outcomes. These studies, however, cannot categorically prove cause‐and‐effect relationships . Interventional study designs can vary from short‐term studies, when the immediate effect of the intervention is investigated within few hours to as long as 24 or 48 h postprandial (i.e., meal/food item consumed once), to long‐term studies that evaluate the effects of the intervention over a period of weeks, months, or years .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, an increased risk of estrogen receptor-negative breast cancer was observed in women who were committed to a diet high in grains, dairy, and sugar and low in vegetables and fish [30]. A dose-response meta-analysis investigating the relationship between egg consumption and the risk of breast, prostate, and ovarian cancers revealed non-significant increase in breast cancer risk, although it was suggested that a positive association between egg intake and fatal prostate and ovarian cancers with an increase in egg consumption to five eggs per week could not be ruled out [31]. Furthermore, the association between dietary fiber intake and the risk of ovarian cancer was observed in a meta-analysis of 19 studies involving 567,742 participants [32].…”
Section: Nutrition and Cancer Riskmentioning
confidence: 99%